RELIGIOUS VALUES IN FOLKLORE OF KANG CIDRA IN PANCASILA CHARACTER EDUCATION - Seruni Widawati; Sugeng Nugroho (Universitas Negeri Medan, 2023)
This study aims to analyze the religious values contained in the Wahyu puppet show of Kang Cidra’s student play Nyi Lucia Siti Aminah Subanto which can be the basis for the development of pancasila character education. Religious values in Catholicism include various aspects related to faith deepening and spiritual strengthening. This play is interesting to study because it is a representation of the sacred event of the crucifixion of Jesus Christ, so it contains teachings on religiosity that serve as a subject of faith for Catholics. The meaning of religious values is analyzed through dramatic structures and textures. The result of this study is that this play contains religious values, including: love, repentance, and loyalty. This value can be lived in everyday life as a development of character education for Catholics. The play Siswa Kang Cidra contains a meaning to invite Catholics to appreciate suffering through the story of the passion and death of Jesus Christ. On the other hand, this play also reveals a reflection of the inner religious attitude shown through Jesus’ disciples. God’s love and forgiveness is very clear in how God still accepts Peter even though he has denied it. This event changed Peter to repent and live by the teachings of Christ until the end of his life. Meanwhile, the act of betrayal by Judas was a reflection of the failure of the faith process. Repentance is the path to blessing because God always accepts repentant humans. The failure of the faith process is a sign that closeness to God is always faced with trials and obstacles. Misguidance due to trials and obstacles can occur if faith is weakened, and weakened faith allows people to make decisions that deviate from the teachings of Christ. For this reason, learning from the failure of the faith process is an effort to strengthen the belief that humans follow and proclaim the teachings of Jesus Christ. The religious values contained in the play include: loyalty, love, and repentance. These values can be lived out in everyday life as the development of Pancasila character education.